Determination of association between some caries-related factors in permanent teeth with body mass index of female school students in Tehran, Iran - Mozhgan Faezi; Nooshin Jalayer Naderi; Salimeh Lashkari (Isfahan University of Medical Sciences, 2013)
Introduction: Some investigations have shown a direct and significant correlation between BMI (body mass index) and dental caries. The aim of this study was to determine the association between obesity and dental caries in the permanent teeth of 12‒14-year-old female students of guidance schools in districts 5 and 6 in Tehran, Iran in 2011.Materials and Methods: In this cross-sectional descriptive study, 950 female students, aged 12‒14 years old, were selected randomly from guidance schools in districts 5 and 6 in Tehran. The frequency of brushing, flossing, daily consumption of snacks, DMFT (Decayed, Missing, Filled) and BMI were assessed using interviews and clinical examinations. The association of the variables was determined by Pearson's correlation and linear regression statistical tests at a confidence interval of 95%.Results: The means of DMFT index were 3.56 ± 2.652, 4.26 ± 2.961 and 4.38 ± 2.899 in 12-, 13- and 14-year-old students, respectively. Evaluation of the effect of demographic variables, oral hygiene habits and obesity on DMFT showed that age (p value = 0.001), toothbrushing frequency (p value = 0.025) and frequency of snack consumption daily (p value = 0.043) are effective on tooth decay. However, no correlation was found between frequency of flossing (p value ≤ 0.083) and BMI (p value ≤ 0.205) with tooth decay.Conclusion: There was no statistically significant association between DMFT and BMI of 12‒14-year-old female students in Tehran. There was no relationship between the frequency of sweet snacks consumption and age with BMI. Toothbrushing frequency and frequency of sweet snacks consumption have an effect on tooth decay. Key words: Body mass index, Dental caries, Obesity